DIAGNOSTIC ACCURACY OF ULTRASOUND FOR MORBIDLY ADHERENT PLACENTA - Ahmed, Aliya; Ayesha Isani Majeed; Ramish Riaz; Hamna Abid; Bilal Asif; Ummehabiba malik (Journal of Ayub Medical College Abbottabad, 2026)
Background: Morbidly adherent placenta (MAP), including placenta accreta, increta, and percreta, is a serious obstetric condition associated with significant maternal morbidity and mortality. The aim of this cross-sectional validation study was to assess the diagnostic accuracy of ultrasound, using the Placenta Accreta Index (PAI), in detecting morbidly adherent placenta (MAP) in a tertiary care hospital in Pakistan. Methods: A total of 81 pregnant women in the third trimester, at risk of developing MAP due to a history of two or more cesarean sections, placenta previa, or prior myomectomy independent of cesarean sections, were included in this cross-sectional Validation study. Gray scale and Doppler ultrasound were performed, and the PAI was calculated. Per-operative findings were considered as the gold standard and compared with ultrasound results. Sensitivity, specificity, and diagnostic accuracy were calculated using a 2x2 contingency table. Results: Among the included women, 25 (30.86%) had confirmed MAP based on perioperative findings, with varying degrees of placenta accreta (percreta, increta, and accreta). The ROC curve analysis revealed a PAI cutoff value of 4.37, yielding a sensitivity of 84.00%, specificity of 85.71%, and diagnostic accuracy of 85.19%. Lacunae, bridging vessels, and placenta previa were found to be associated with increased risk of MAP, while decreased myometrial thickness correlated with higher PAI values. Conclusion: This study demonstrates that ultrasound, utilizing the PAI, exhibits promising diagnostic accuracy for detecting morbidly adherent placenta in women at risk. The findings support the role of ultrasound as a valuable tool in the diagnosis of MAP, aiding in appropriate management and intervention.